Controlled Manipulation of Vortices in 3D/2D Superconducting Samples. (Manipulación controlada de vórtices en muestras superconductoras 2D/3D.) - González Acosta, J.; Aguilar Siado, J.; Barba Ortega, J. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
AbstractIt is well-known that the time dependent Ginzburg-Landau theory is a reliable theoretical tool to investigate the Shubnikov state in a superconductor sample in presence of an external applied magnetic field. In this work, we solved the system of the Ginzburg-Landau equations in two and three dimensions for two particular cases: For a parallelepiped with volume Vp, with transversal area Sp = 9ξ 2 (0), 36ξ 2 (0) and height hp = 1ξ (0), 6ξ (0), where ξ (0) is the coherence length. In the other hand, for a thin disk with a centered circular and triangular defect, with topology of dot/anti-dot. In both cases are immersed into a homogeneous magnetic field. The effects of pinning/anti-pinning forces due to defects in the disk and demagnetization effects due to the finite size of the parallelepiped on configuring vortices and critical fields are discussed. In the tridimensional case, the magnetic field and the order parameter are not invariant along the direction z. ResumenEs bien conocido que la teoría de Ginzburg-Landau es una herramienta teórica confiable para investigarel estado de Shubnikov en muestras superconductoras en presencia de campos magnéticos aplicados. Eneste trabajo resolvemos el sistema de ecuaciones Ginzburg Landau en dos y tres dimensiones en dos casos particulares: para un paralelepípedo de volumen Vp, con área transversal Sp = 9x 2(0), 36x 2(0) y altura hp = 1x (0), 6x (0), donde x (0) es la longitud de coherencia y por otra parte, para un disco fino con un defecto circular y triangular centrado con topología punto/anti-punto. En ambos casos las muestran estan submersas en un campo magnético homogeneo. Los efectos de las fuerzas de anclaje/anti-anclaje debido a los defectos en el disco y los efectos de demagnetización debido al tamaño finito del paralelepipedo sobre la configuración de vortices y campos críticos son discutidos. En el caso tridimensional, el campo magnético y el parámetro de orden no son invariantes a lo largo de la dirección z.